2014
DOI: 10.4028/www.scientific.net/amm.641-642.1172
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electric Conductivity of Urban Stream Water Polluted with Municipal Effluents

Abstract: Specific electric conductivity of water samples in a polluted urban stream was compared with other water quality parameters such as concentration of inorganic carbon, total organic carbon, and total nitrogen. Increasing of water conductivity 1.3...10 times was observed downstream canalization outlets discharging drainage waters together with residential waste waters from inhabited district of city. In some periods water conductivity showed good correlation with pollutants concentration such as TN and IC (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The PCA analysis showed that distance from the study sites to built-up areas and conductivity were the main factors contributing to their separation. The significance of distance from the study sites to built-up areas and increasing of conductivity was already highlighted by other authors (Chusov et al 2014;Moreyra and Padovesi-Fonseca 2015;Prescott and Eaton 2018). According to some authors (Novikmec et al 2016) proportion of urban land was positively related with water conductivity, i.e., water ecosystems with high proportion of urban areas in their catchments were characterized by high values of conductivity.…”
Section: Environmental Difference Between Rural and Urban Samplessupporting
confidence: 55%
“…The PCA analysis showed that distance from the study sites to built-up areas and conductivity were the main factors contributing to their separation. The significance of distance from the study sites to built-up areas and increasing of conductivity was already highlighted by other authors (Chusov et al 2014;Moreyra and Padovesi-Fonseca 2015;Prescott and Eaton 2018). According to some authors (Novikmec et al 2016) proportion of urban land was positively related with water conductivity, i.e., water ecosystems with high proportion of urban areas in their catchments were characterized by high values of conductivity.…”
Section: Environmental Difference Between Rural and Urban Samplessupporting
confidence: 55%
“…(2020) 2:1788 | https://doi.org/10.1007/s42452-020-03572-7 Thus, the mean conductivity values for water from Ureje and Awedele from this study indicate augmented levels of nutrients, salts and impurities. In other studies, increased conductivity of surface water downstream canalization outlets that discharge drainage and stormwaters from urban settlements have been reported [19,34]. Observations for heavy metals in surface water samples revealed that all metals measured were within WHO specified limits, except Pb, Cd, Fe and Mn in surface water of both rivers which were above the recommended limits.…”
Section: Surface Water Quality Across Sitesmentioning
confidence: 67%
“…In natural streams, conductivity tends to be low in headwater reaches and then increase in downstream reaches, especially when streams pass through urban areas ( Chusov, Bondarenko & Andrianova, 2014 ). However, previous studies of effluent-fed streams have reported elevated conductivities near outfalls and then relatively stable values downstream ( Chen et al, 2009 ; Prat et al, 2013 ; Matamoros & Rodríguez, 2017 ).…”
Section: Discussionmentioning
confidence: 99%